Emerging Issues in Banking Regulation - Sharma, Sunil (IMF Working Papers; Working Paper ;, 2003)
The paper provides an overview of the profound and rapid changes in banking brought about by technology and deregulation, and discusses the hurdles that will have to be negotiated for putting in place the three pillars-capital adequacy rules, supervision, and market discipline-of the bank regulatory framework envisioned by the New Basel Accord (Basel II). It argues that, especially for developing countries, finding the right balance between regulation, supervision, and market discipline is likely to be difficult. Considerable technical expertise as well as political discipline-which can be viewed as a fourth pillar-will be required to implement Basel II.